2019
DOI: 10.1002/ajmg.a.61217
|View full text |Cite
|
Sign up to set email alerts
|

A heterozygous, intragenic deletion of CNOT2 recapitulates the phenotype of 12q15 deletion syndrome

Abstract: Only a few individuals with 12q15 deletion have been described, presenting with a disorder characterized by learning disability, developmental delay, nasal speech, and hypothyroidism. The smallest region of overlap for this syndrome was included in a genomic segment spanning CNOT2, KCNMB4, and PTPRB genes. We report on an additional patient harboring a 12q15 microdeletion encompassing only part of CNOT2 gene, presenting with a spectrum of clinical features overlapping the 12q15 deletion syndrome phenotype. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 10 publications
2
20
0
Order By: Relevance
“…The phenotypes of the patient we have documented herein with a heterozygous nonsense variant in the CNOT2 gene itself and of three recently documented patients with a microdeletion in the chromosomal 12q15 region including the CNOT2 gene (Alesi et al, , ; Uehara et al, ) significantly overlap each other (Table ). The phenotypic spectrum of the newly recognized disorder consists of a language development delay and characteristic facial features including upslanted palpebral fissures, anteverted nares, a thin upper‐lip, and micrognathia.…”
Section: Summary Of the Patients With Cnot2 Haploinsufficiencymentioning
confidence: 60%
See 3 more Smart Citations
“…The phenotypes of the patient we have documented herein with a heterozygous nonsense variant in the CNOT2 gene itself and of three recently documented patients with a microdeletion in the chromosomal 12q15 region including the CNOT2 gene (Alesi et al, , ; Uehara et al, ) significantly overlap each other (Table ). The phenotypic spectrum of the newly recognized disorder consists of a language development delay and characteristic facial features including upslanted palpebral fissures, anteverted nares, a thin upper‐lip, and micrognathia.…”
Section: Summary Of the Patients With Cnot2 Haploinsufficiencymentioning
confidence: 60%
“…CNOT2 had previously been reported to be one of the causative genes of major phenotypes of 12q15 microdeletion syndrome (Alesi et al, ). In 2019, after our article was published, Alesi et al reported a patient with syndromic intellectual disability and 85 kb intragenic deletion of CNOT2 (Alesi et al, ). This patient with intragenic deletion of CNOT2 was detected by chromosomal microarray analysis (Alesi et al, ).…”
Section: Summary Of the Patients With Cnot2 Haploinsufficiencymentioning
confidence: 97%
See 2 more Smart Citations
“…CNOT2 is an important regulator for energy metabolism, cellular stress and fatty acid metabolism in the skeletal muscles. The heterozygous intragenic deletion of CNOT2 displayed disordered phenotypes of learning disability, developmental delay, and hypothyroidism [65,66]. TRHDE is an extracellular peptidase that specifically degrades the TRH to regulate appetite and metabolism [67,68].…”
Section: Grip1 Frs2 Cnot2 Trhde Affects Metabolic Processesmentioning
confidence: 99%